Evaluation of Early Growth of Oil Palm Seedlings (Elaeis Guineensis Jacq) In The Pre-Treatment Stage - Abidin, Zainal; Hidayat, Nur; Muh Asdiq Hamsin Ramadan, Laode; Putra Pratama, Adnan (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2025)
Palm oil (Elaeis guineensis Jacq.) is a strategic plantation commodity that plays a significant role in the Indonesian economy. One of the main factors determining palm oil productivity is the use of superior seeds with good initial vigor. This study aims to examine the morphological characteristics of three-month-old oil palm seedlings as an indicator of initial vigor that can be used as a baseline before the application of bio-amelioration technology using zeolite and Lactic Acid Bacteria (LAB) on post-mining land. The study was conducted at the pre-nursery stage by measuring parameters such as plant height, number of leaves, and stem diameter. Data analysis was conducted descriptively by calculating the average value. The results showed that the average seedling height reached 32.5 cm, the number of leaves was 4.2, and the stem diameter was 0.85 cm. These values ​​are within the international standard range for healthy three-month-old seedlings, thus they can be categorized as seedlings with fairly good vigor. This finding is important because initial morphological quality has been shown to have long-term implications for oil palm productivity. Furthermore, this baseline data serves as a benchmark for assessing the effectiveness of zeolite and LAB applications in further research on post-mining land which is generally poor in nutrients, acidic, and heavily degraded. Thus, this study provides an initial contribution to efforts to support sustainable post-mining land revitalization programs through mineral- and microbial-based bio-amelioration approaches.